(3GJMGa GdeQjO HLhgQI GdJhMjOs - (3YHO GdSdGe Hf EHQGgje GdeGdcj GddbGfjs; (3EHQGgje Hf EHQGgje GddbGfj GdeGdcj,J (B1041 (3g` ? s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ GddbGfj bO cfJ dNUJ eG Ydbg CSJGPfG ef YeOI GdeQjO Ydi YbjOJg GdeSeGI HLhgQI GdJhMjO aj ChQGb bdjdI SejJgG EQTGO GdeQjO s
(3BNQgG (B:s
(3eJhSdkG HUGMH GdhSjdI hGebGe GdeMehOGf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds